336 Non- fatal drownings in alberta: characteristics and distribution. (20th November 2022) - Koziel, Jakob; Belton, Kathy; Voaklander, Don; Carter, Kelly
Abstract : Background: Fatal and non-fatal drownings are one of the greatest disease burdens currently affecting the developed and developing world. A 2017 dissertation found that there were a total of 1, 148 non-fatal drowning incidents in Canada, excluding Quebec, between 2008 and 2012 that resulted in ED visits. To date there is no research that has explored the relationships between non-fatal drownings and various aquatic facility variables and the context of these events. The objective of this research is to describe the characteristics and distribution of non-fatal drowning in Alberta aquatic facilities. Methods: Data will be collected from incident reports, completed at the time of a non-fatal drowning event an aquatic facility located in the two major cities; Edmonton and Calgary from 2015–2021. The drat WHO categories for non-fatal drownings will be used in data classification. The current study will utilize descriptive analyses to depict the characteristics of non-fatal drownings. Variables of interest include the age/sex of those rescued, demographic profile of pool participants, age of pool, pool size, staff on duty, time of day and day of week. Results: Preliminary results indicate that males and those less than 18 years of age suffered the highest proportion of non-fatal drowning events. The highest percentage of events occurred in recreational pools as well as during public swims. Further, 89% of these events involved a wet rescue and resulted in mild respiratory symptoms requiring no first aid or ambulance. However 11% of adults had moderate or severe respiratory symptoms. Final results will be available for presentation. Conclusions: While preliminary in nature the results indicate the population and aquatic context that are high risk. More data will allow us to do more rigorous and detailed analysis to inform non-drowning prevention strategies and Alberta pool safety practices. Learning Outcomes: Attendees: will understand characteristics of those experiencing non-fatal drowning will be able to recognize common pool characteristics where individuals are at risk for non-fatal drowing